The Influence of Nurses Performance, Facilities and Service Quality Towards Patient Satisfaction at the Outpatient Installation of Advent Hospital Bandung - Ardi Peterson Seran; Freddy Johanis Rumambi; Nofrisel Nofrisel; Mardi Suharyono; Rudianto Rudianto; Marisi Pakpahan (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Installation take care road is one of facility House the most sick used by clients or patient and also is access First for every patient For get the care needed , so that very important for House Sick For ensure that every means infrastructure , and also the provision of quality human resources For ensure quality service in maintain satisfaction patient . Research This done For know influence partial and simultaneous from performance nurses , facilities , and quality service to satisfaction patient . Research This is study quantitative descriptive , for describe influence between variable X to Y, which is done against 101 patients take care Road in the House Bandung Adventist Hospital , data inside study This collected use questionnaires that have been tested for validity and reliability, which are then processed use SPSS application , and presented in form table . Found that performance nurse No own influence significant to satisfaction patient with mark significant 0.249, while facilities and quality service own influence significant with mark respectively 0.006 and 0.000. In simultaneous performance nurses , facilities and quality service own influence significant with value 0.000 with 67.9% of satisfaction patient explained by the variables discussed in study this . Satisfaction patient influenced by performance nurses , facilities , and quality service in a way together , because That important for House Sick For Keep going maintain and improve it .